Non-inferiority comparison of medical glue and hook-wire for preoperative localization of multiple pulmonary nodules - Xie, Zexin; Ma, Ran; Gao, Tao; Liu, Jingsong; Zhang, Kewei; Li, Jun; Zhou, Xiaotong; Zhang, Hao (Frontiers in Surgery, 2025)
BackgroundVideo-assisted thoracoscopic surgery is a widely employed minimally invasive approach for resecting pulmonary nodules. However, precisely localizing deep-seated or poorly visualized nodules remains a prominent challenge. This study aims to compare the effectiveness and safety of medical glue vs. hook-wire in the CT-guided localization of multiple pulmonary nodules.MethodsA prospective cohort of patients scheduled for CT-guided localization of multiple pulmonary nodules between February 2024 and August 2024 was enrolled. Patients were randomized into a medical glue group and a hook-wire group in a 1:1 ratio. The primary endpoint was the localization success rate, with the objective of conducting a non-inferiority comparison of medical glue and hook-wire for the preoperative localization of multiple pulmonary nodules at a non-inferiority margin of 10%. Secondary endpoints consisted of complication incidence following localization and pain scores assessed via the Numerical Rating Scale.ResultsMedical glue demonstrated non-inferior success rates vs. hook-wire [97.5% vs. 95%, absolute difference = 2.5%, 95% CI (−5.82%, 10.82%); P = 1.00]. Although overall complications were comparable (42.5% vs. 55.0%, P = 0.263), medical glue significantly reduced pneumothorax (22.5% vs. 47.5%, P = 0.019) and pulmonary hemorrhage (7.5% vs. 27.5%, P = 0.019). Patients receiving medical glue reported lower 2 h pain scores (2.70 ± 0.76 vs. 3.71 ± 1.42, P = 0.007).ConclusionsThe application of medical glue for the CT-guided localization of multiple pulmonary nodules demonstrated a non-inferior success rate comparable to that of hook-wire. Furthermore, compared to hook-wire, medical glue was associated with a lower incidence of pneumothorax and pulmonary hemorrhage, as well as reduced pain scores at 2 h post-localization.Clinical Trial Registrationhttps://www.chictr.org.cn, identifier (ChiCTR2400080040).